AN AHP BASED EXPERT STUDY OF INTRINSIC PSYCHOLOGICAL DETERMINANTS OF APPAREL PURCHASES IN AN INDIAN METROPOLITAN CITY - Maiti, Bratin; Majumdar, Malini; Basu, Protik (International Journal of Research -GRANTHAALAYAH, 2025)
In today’s competitive market, understanding the drivers of consumer purchase decisions is critical for the retailers. This study uses an expert based Analytic Hierarchy Process (AHP) to prioritize six intrinsic psychological factors namely motivation, attitude, perception, learning, personality and self-esteem believed to influence apparel purchase decisions in Kolkata’s organized retail sector. Three domain experts selected on the basis of their experience provided pairwise comparisons. Group judgments were aggregated using the geometric mean method. Individual and aggregated values of maximum eigenvalue (λ max), consistency index (CI) and consistency ratio (CR) were computed. All CR values were below 0.10, indicating acceptable consistency of expert judgments. Final AHP results revealed motivation (44.72%) as the most influential factor, followed by attitude (24.30%), perception (14.42%), self-esteem (7.43%), learning (7.05%), and personality (3.45%). Results of the study suggest marketers to concentrate on motivational stimuli, attitudinal interventions, perceptual cues and communication strategies to influence customers for purchase. However, small expert panel, lack of direct consumer feedback and confinement to one city are limitations of the study. Future studies with more experts and consumer feedback across different cities can validate the findings. Multi-criteria decision approach for pair wise comparison and ranking of internal factors adds to the literature in the area of consumer psychology. The study provides practical recommendation to the marketers to shape consumer perception and their purchase behaviour.